The influence of phase change material filled three-dimensional printed artificial aggregates on the properties of blast furnace slag based alkali-activated concrete - Omur, Tarik; Akpunar, Ahmet Kaan; Bingol, Ayse Betul; Oktay, Buesra; Ustundag, Cem Bulent; Kabay, Nihat (HIGHER EDUCATION PRESS, 2025)
This study proposes the use of three-dimensional (3D) printed artificial aggregates as phase change material (PCM) carriers and investigates its effects on alkali-activated slag concrete. The artificial aggregates were manufactured using Fused Deposition Modeling (FDM) and Stereolithography (SLA) techniques and PCM was injected into the artificial aggregates. Natural aggregates were replaced with FDM or SLA-type artificial aggregates by 15% and 30% by volume and alkali activated slag concrete specimens were produced. The characteristics of artificial aggregates and their impact on mechanical, physical, and thermal properties of concretes are examined. The results showed that 3D-printed artificial aggregates ameliorated the abrasion resistance of concrete specimens. The concrete samples had a minimum strength of 32 MPa after 28 d, with 15SLA concrete achieving 42.5 MPa, which is comparable to the reference concrete. Thermal test results demonstrated that the PCM helps maintain the concrete surface temperature 3.7 degrees C higher than the reference mix when the ambient temperature drops below zero and notably slows down the temperature decrease. The concrete mixes without PCM showed ice formation on their surfaces when the ambient temperature dropped to -5 degrees C, while no ice formation was observed on samples incorporating PCM. Furthermore, the inclusion of PCM improved the freeze-thaw resistance of concretes.
Keywords: 3D-printing; artificial aggregate; phase change materials; alkali-activation; THERMAL-ENERGY STORAGE; PCM; Engineering